The Dynamics of Interprofessional Relationships within Hospital Medical Teams: A Case Study in Tasikmalaya - Peni Cahyati; Tetet Kartilah; Sofia Februanti; Iwan Somantri; Heri Djamiatul Maulana; Novi Enis Rosuliana (International Journal of Psychology and Health Science, 2026)
Interprofessional relationships within medical teams are a key determinant of healthcare service effectiveness in hospitals. This study aims to examine the dynamics of interprofessional relationships in two hospitals in Tasikmalaya: RSUD Dr. Soekardjo and RS Jasa Kartini. A qualitative case study approach was employed to explore the experiences of medical personnel, involving 15 informants from various health professions through in-depth interviews, non-participant observations, and document analysis. Data were analyzed using Braun and Clarke’s thematic analysis. The findings reveal that interprofessional relationships are still predominantly shaped by hierarchical structures, with physicians assuming leading roles in formal settings, while informal interactions exhibit more egalitarian collaboration. Communication barriers including reluctance to challenge doctors' opinions and miscommunication of medical terminology emerge as key challenges to service coordination. The bureaucratic organizational culture in public hospitals reinforces hierarchical dynamics, whereas private hospitals demonstrate greater flexibility yet maintain the dominance of certain medical professions. Local Sundanese cultural values, which emphasize politeness, also influence communication patterns that avoid open confrontation. Individual adaptive strategies such as informal communication channels and participation in collaborative training have emerged as efforts to overcome systemic barriers. This study concludes that improving interprofessional relationships in hospitals requires organizational culture transformation, enhanced cross-professional communication skills, and collaborative training that is sensitive to local sociocultural contexts.